(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this study, we employ the generalized Mittag-Leffler function and the Komatu integral operator to present a new linear operator in terms of the convolution and define related classes of admissible functions. Then, we derive several properties and characteristics of two-order differential subordinations and superordinations. Moreover, we establish sandwich-type results for a class of analytic functions on an open unit disc. Over and above, we derive various results involving univalent functions in some details.